O ensino de Geografia e a linguagem cartográfica: os mapas mentais e sua contribuição para a formação continuada de professores da educação básica - Lopes, Alyne Rodrigues Cândido (2018)
This work presents a discussion about the continuous formation of teachers and the importance of the work with the School Cartography in the formation of these professionals. It is important to include in Geography classes other forms of cartographic representations in addition to the finished maps. It is in this sense that we propose mental maps, since they allow the expression and improvement of knowledge about space, specifically about the lived space. The teacher needs to learn and know how to use this resource in the classroom and for this we try to approach this type of representation of teaching practices through the continuous formation. Thus, the general objective of this work is to increase the use of mental maps in the teaching of Geography through the continuous formation of teachers of the final years of Elementary School. For that, it was put as fundamental: to reflect upon the use of cartographic language in Geography teaching; to understand and analyze the proposals of elaboration and interpretation of mental maps within the perspective of collaborating with the teaching-learning process of Geography; and to contribute to the continuing education of Geography teachers in relation to working with the cartographic language and its potential with the teaching of school contents. The present study is supported by the qualitative research approach and the participatory research modality. As a methodological path it was carried out the literature review, construction and development of a mini-course, application of mental maps to the students and interviews with the teachers. The interviews were made, initially, before the mini-course, in order to find out how was their initial training in relation to Cartography and wether they already knew the proposal of mental maps; and again, after the mini-course, to know if we had reached our goals for the continuing education course. We propose a didactic referral by means of two proposals of mental mapping, aiming to contribute to the work of teachers in the use of this resource in Geography classes.